Pengembangan Kurikulum Terpadu Pada SMP Islam YLPI Pekanbaru: Pengembangan Kurikulum Terpadu Pada SMP - Ali Riswan, Muhammad (MGMP PAI SMP BINTAN, 2023)
The development of an integrated curriculum at the Yayasan Lembaga Pendidikan Islam (YLPI) Pekanbaru is the main focus in efforts to improve the quality of education. The integrated curriculum integrates various subjects into a coherent whole, allowing students to gain a comprehensive understanding and cross-disciplinary skills. This research uses a qualitative descriptive method with data collection through observation, interviews, and document analysis. The research sample includes students, teachers, and curriculum management staff at YLPI Pekanbaru. The research results are expected to contribute to the development of an integrated curriculum at YLPI Pekanbaru and provide insights for other educational institutions in improving their quality of education. Keywords: Development; Curriculum; integrated; SMP; YLPI;